The Current State of Vaccine Development for Specific Prophylactics of Arenaviral Hemorrhagic Fevers - T. E. Sizikova; V. N. Lebedev; S. I. Syromyatnikova; S. V. Borisevich (Проблемы особо опасных инфекций, 2018)
Presently, the Arenavirus genus (Arenaviridae family) includes 26 individual species of viruses. It is divided into two main groups – Old World arenaviruses and New World arenaviruses. The New World arenaviruses comprise four clades: А, B, C, D; pathogenic for humans New World arenaviruses are attributed to clade B. Lassa, Lujo, Machupo, Junin, Guanarito and Sabia viruses are the agents of extremely hazardous hemorrhagic fevers (Lassa hemorrhagic fever, Lujo hemorrhagic fever, Bolivian hemorrhagic fever, Argentinean hemorrhagic fever, Venezuelan hemorrhagic fever, Brazilian hemorrhagic fever, accordingly). These arenaviruses pose a potential threat to national public health due to the possibility of their accidental importation into the territory of the Russian Federation. The vaccination of risk group is the most effective and money-saving means of protection against epidemic spread. Objective of this review is to analyze the specific preparations for arenaviral hemorrhagic fever prevention that are currently under development. Production of live vaccines based on attenuated strains of the agents, the DNA vaccines, vector recombinant vaccines and vaccines on the basis of RNA-replicons is viewed as the main trends in the area. Тhe most important results in the development of effective prophylactic means against arenaviral hemorrhagic fevers are discussed in this paper.